The Production of Knowledge in Work Teams: The View from Below - Sharon L. Howell (Adult Education Research Conference, 2001)
This paper examines the experiences of entry level hourly wage workers in a workplace shaped by the "excellence" movement. Their micro-level encounters with the "new work order" are set within the macro-level economic, political and cultural context that structures the work experience.